2013
DOI: 10.1007/s10705-013-9550-4
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional feeds for small ruminants in dry areas have a minor effect on manure nitrogen flow in the soil–plant system

Abstract: In dry areas, unconventional feeds are increasingly used for mitigating feed shortages and rangeland degradation. We evaluated how feeding sheep diets containing olive leaves, saltbush leaves and olive cake affects manure quality compared to a barley straw based diet. Soil incubation and plant growth experiments were carried out to measure soil nitrogen (N) mineralization and N uptake by barley plants and to calculate N flow through the feed-animal-soil-plant system. Fresh feces, composts consisting of feces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…N content of the shoots was measured with a CN analyser (Flash EA, 1112 series) [42]. As reference plant material Alfalfa was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…N content of the shoots was measured with a CN analyser (Flash EA, 1112 series) [42]. As reference plant material Alfalfa was used.…”
Section: Methodsmentioning
confidence: 99%
“…After drying, shoots were ground using a swing mill (Retsch MM200, Retsch GmbH, Haan, Germany) with a frequency of 25 s −1 for one minute. N content of the shoots was measured with a CN analyser (Flash EA, 1112 series) [ 42 ]. As reference plant material Alfalfa was used.…”
Section: Methodsmentioning
confidence: 99%
“…One such example is phenols, especially condensed tannins, which may firmly bind to proteins. Manure from diets rich in such compounds was sometimes Abbeddou et al, 2013), but not always (Tiemann et al, 2009), shown to have a lower plant N fertilizer value, a phenomenon Estermann et al, 2002;Śliwiński et al, 2004;Hindrichsen et al, 2005Hindrichsen et al, , 2006Machmüller et al, 2006;Van Dorland et al, 2007;Klevenhusen et al, 2011 Total gaseous N emissions Model manure storage with mass balance Estermann et al, 2002;Śliwiński et al, 2004;Van Dorland et al, 2007 NH 3…”
Section: Specific Information Gathered By Measuring N Emission and Fementioning
confidence: 99%
“…Comprehensive analyses have to consider total farm system N efficiency. Although urine N is likely best used by the plants, N use efficiency cannot be fully and reliably predicted from this information, because the fertilizer value is a complex matter including C:N ratio, phosphorus content, and anti-nutritional compounds possibly hampering plant growth and thus N utilization (Abbeddou et al, 2013).…”
Section: Emissionsmentioning
confidence: 99%